2015
DOI: 10.1177/0021998315604039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative low-velocity impact response of textile-reinforced concrete and steel-fiber-reinforced concrete beams

Abstract: In this study, the effect of the textile reinforcement type on the flexural response of textile-reinforced concrete beams under static and impact loads was investigated. In addition, to compare the flexural capacities with those of conventional steel-fiber-reinforced concrete, steel-fiber-reinforced concrete beams having similar compressive strength with that of textile-reinforced concrete were fabricated and tested according to the fiber content. Enhancements in the flexural capacities were obtained using pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
1
6
0
4
Order By: Relevance
“…This character of the curves in Fig. 6 also appeared in the test data on steel fiber reinforced concrete previously reported by Yoo et al [17]. As stated in that study, matrix softening and fiber bridging effect dominates bending behavior when the first crack occurs.…”
Section: Resultssupporting
confidence: 84%
“…This character of the curves in Fig. 6 also appeared in the test data on steel fiber reinforced concrete previously reported by Yoo et al [17]. As stated in that study, matrix softening and fiber bridging effect dominates bending behavior when the first crack occurs.…”
Section: Resultssupporting
confidence: 84%
“…This study showed that the usage of 3D-TF gives greater improvement in bending strength and toughness than 2D-TF. In the same time, the usage of 0.5 % of steel-fiber gives greater bending strength and toughness than both 3D-TF and 2D-TF [14].…”
Section: Mechanical Behaviors Of 3d-tfrcmentioning
confidence: 91%
“…Besides, compared to specimens without steel fibers, the addition of steel fibers has higher static compressive strength. This is due to the fiber bridging against the further development of cracks (Yoo et al, 2016).…”
Section: Quasi-static Compressive Strengthmentioning
confidence: 99%